Digital Media of Aliansi Laki-Laki Baru in Design Studies: Building a New Image of Men (?) - Utomo, Samuel (Universitas Ciputra, 2023)
This research seeks to elucidate digital feminist activism in the context of user interface design and content within the study of design, exploring the visual representation on the Alliance of New Men (ALB) website. The qualitative research method employed in this study, which includes a literature review, indicates that digital feminist activism within the user interface explains that the ALB website demonstrates a multi-faceted identity that cannot be confined to a single website characteristic. The website's user interface is more intuitive compared to offering a distinct uniqueness that deviates from the dominant values of ALB. On one hand, the ALB website's user interface breaks rigid boundaries in its layout flexibility, yet on the other hand, it still reflects the meaning of traditional gender stereotypes through color usage. The content related to domestic space in ALB appears to merely reverse roles, but it ultimately reverts to traditional codes of masculinity.